Integrating Islamic Ethical Principles into Early Childhood Education Governance: A Case Study of PIAUD Institutions in Indonesia - Ahmad Syukron; Syafruddin; Ahmad Paridi; Chindya Pratisti Puspa Devi; Hilman Mi'roji (Universitas Muhammadiyah Malang, 2025)
This study examines the implementation of good governance in Early Childhood Education (ECE) institutions, with a particular focus on Islamic Early Childhood Education (PIAUD) in Indonesia. ECE is a critical stage in shaping children’s holistic development, and its sustainability is not only determined by learning programs but also by effective governance systems. The research employed a qualitative case study approach, involving 12 institutions in West Java selected based on operational maturity, organizational structure, and management diversity. Data were collected through in-depth interviews, participant observation, and document analysis, and validated through triangulation and member checking. The findings reveal that transparency is the most challenging governance principle, especially in financial management, while accountability in learning quality and parental involvement show stronger outcomes. Stakeholder participation highlights the active role of parents, teachers, and foundations, although community and government engagement remain limited. Efficiency in managing time and facilities is relatively good, but human resource management requires significant improvement. Importantly, the integration of Islamic values such as amanah (trust), ‘adl (justice), and syura (consultation) enriches governance practices and enhances institutional integrity. The study contributes to both theory and practice by offering an integrated governance model that combines universal principles with Islamic values, providing a moral-spiritual framework for strengthening leadership, accountability, and sustainability in ECE institutions. The findings have practical implications for policymakers and practitioners in designing governance strategies that are both contextually relevant and ethically grounded.